Geopolitics and the ASEAN single aviation market: Aspirations versus realities - Zuan, Haris; Ellis, Darren; Pagliari, Romano (Elsevier, 2021)
This paper aims to explore and identify the key geopolitical barriers and opportunities to greater regional integration amongst the Association of Southeast Asian Nations (ASEAN) member states by examining the case study of the ASEAN single aviation market (ASAM). This paper is based on an ongoing doctoral research project covering the topic. To date, ASEAN has implemented substantial liberalisation of its regional air transport market via an open skies policy, included as part of the ASEAN Community Project. This aims to not just foster connectivity and economic development, but ultimately to contribute to the building of a regional identity. While there has been some evident progress since the launch of the initiative in the region, the open skies agreement promoted as ASAM has not gained as much traction as projected, nor achieved its core stated aim of creating an effective single air transport market; a stated goal it initially planned to achieve by the end of 2015. Most of the literature explaining the divergence between key aspirations and realities in ASAM focuses on the economic regulation of international air transport in the region, and typically discusses these core considerations from the perspectives of law and policy. There are few substantial scholarly works that incorporate geopolitics, aeropolitics and/or diplomacy, all of which are important variables closely linked to the field of international relations. The geopolitical perspective on ASAM is still largely understudied, and this paper and the evolving research underpinning it, are intended to contribute to that identified gap.
Keywords: geopolitics; ASEAN; ASAM; single aviation market; regional multilateralism; ASEAN way